Concubine mother-daughter attachment in Amy Tan’s the Joy Luck Club and Pramoedya Ananta Toer’s This Earth of Mankind - Li, Meihua; Noor, Rohimmi (Penerbit Universiti Kebangsaan Malaysia, 2025)
The mother-daughter relationship is one of the most primary bonds. It is also an embodiment of women alliance. The mother-daughter interaction is manifested intensively in Amy Tan’s The Joy Luck Club and Pramoedya Ananta Toer’s This Earth of Mankind. This study compares two pairs of mothers and daughters by looking at their lives. According to John Bowlby’s attachment theory(1982), a mother’s past personal, cultural and economic experiences would significantly impact her caregiving style. The intersection of the personal, the cultural and the economic catches every mother. Kimberle Crenshaw’s intersectionality (1989) is introduced to study the concubine mothers’ pasts. A mother’s maternal care directly impacts a child’s attachment pattern. As a result of various attachment patterns, children’s later personality exhibits different dynamics( Bowlby, 1982). This study identifies the concubine mothers’ respective intersectional life, namely one in the patriarchal and traditionally feudal system, and the other in feudal and colonial system. And that determines their parenting ways towards their daughters, which facilitates the formation of the daughters’ attachment patterns: the secure and the anxious-resistant. Later, the daughters’ personalities demonstrate a contrasting development. An-mei becomes strong-minded, composed and highly resilient, whereas Annelies develops into a mentally vulnerable, impulsive and less resilient person. By focusing on the experiences of the female characters, this study acknowledges women’s intersectionality and female subjectivity. By locating them in Asian background, it helps with the understanding of Asian women’s life and Asia’s diverse culture.